El uso del espanglish en la publicidad en Costa Rica - Smith, Andrew (2015)
This paper will study the use of Spanglish in Costa Rican advertising. The significance of this research lies in the fact that although Spanglish is commonly found in Latin American Spanish, especially in advertising, the relationship of these two fields has rarely been analyzed in Costa Rica. Thus, this study can provide important insights into the use of Spanglish and its impact on advertising in commercial and social terms.